Sustainability Issues on Residential Area Policies in Indonesia: How Adaptive They Are? - Pitri Yandri; Dominicus Savio Priyarsono; Akhmad Fauzi; Arya Hadi Dharmawan (Jurnal Studi Pemerintahan, 2018)
Regulation is one of the important instruments in generating good governance, including the governance of residential area in order to achieve sustainable development. In Indonesia, however, the sustainability issue of residential area does not get any serious attention, especially from the perspective of policy. This article elaborates the regulation related to the issue of sustainable residential area. The results of the review show that all residential area regulations, both in the central and local governments, have not been adaptive against issues of sustainability. Detailed elaboration of the findings is discussed further in this article.